Penerapan Program Metode Ummi dalam Pembelajaran Membaca Al-Qur’an di SDIT Widya Cendekia (Pengenalan Lapangan Persekolahan di SDIT Widya Cendekia Kelompok 44) - Enung Nugraha; Egi Desabina; Ningrat Haeliah; Nadya Fatimaturohmah; Melinda Melinda; Ulfa Masfufah; Monica Mastuti Ubudiah; Nurkhotimah Nurkhotimah; Nurlaila Harum; Siti Mahilatul Azizah; Octavia Pradya Sinta; Shiyam Putri Utami; Siti Afuah (Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to determine the application of the Ummi method program in learning to read the Qur'an by SDIT Widya Cendekia students and the results obtained from the Ummi method. In carrying out this study the authors used qualitative research this study uses data collection techniques, namely observation, interviews, and documentation. After the data is obtained, the data is processed with several techniques, namely editing and data interpretation. Furthermore, all data were analyzed using qualitative descriptive techniques. The results of this study indicate that the application of the Ummi method program has good results so that it has a good effect on students at Sdit Widya Cendekia.